Literature Review on the 4 Days Work Week (4DWW) System to Improve Worker Productivity and Well-Being - Joko Purnomo; Nur Wening; Sujoko Sujoko (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines the 4-Days a Week (4DWW) system, an innovative work approach that aims to improve employee productivity and well-being. By reviewing the literature on the implementation of 4DWW in different countries and industries, the study identifies the benefits, challenges, and implications of transitioning to this model, particularly in the post-pandemic context. The study used a qualitative literature review, analyzing academic articles and case studies from SCOPUS-indexed journals. This research ranges from the early implementation of 4DWW in the 1970s to recent studies conducted after the COVID-19 pandemic. This research focuses on the impact of 4DWW on employee productivity and well-being. The 4DWW system significantly improves work-life balance and reduces employee stress, leading to better mental health and higher satisfaction. Productivity often increases due to shorter and more focused work periods. However, the challenges include managing work intensity and ensuring operational continuity, particularly in sectors that require a high physical presence. The study offers a comprehensive review of global research on 4DWW, which presents a holistic perspective on its potential benefits and drawbacks. The new thing lies in efforts to overcome the resurgence of interest in 4DWW post-pandemic and evaluate its feasibility in the modern work environment. The findings show that 4DWW can redefine the work paradigm, emphasizing quality over quantity while fostering a healthier and more sustainable work culture. The study underscores the need for legislative support, effective communication strategies, and tailored implementation plans to ensure a successful transition across a wide range of industries.